What Science Knows and How It Knows It by James Franklin - Bauer, Henry (Journal of Scientific Exploration, 2017)
Extreme views about science are widespread. The media, policy makers, self-styled “skeptics” and a variety of other science groupies take any contemporary scientific consensus as Gospel truth. Some go so far as to attempt to censor those who question mainstream dogmas, labeling them “denialists”, the modern term for heretics, even as the actual evidence gives good grounds for holding the mainstream consensus as at best inadequate (Bauer 2012). At the other extreme are the postmodernists, New Agers, and proponents of the “strong programme” in sociology of science, who deny that science can offer any authentic knowledge or understanding of reality. The rational middle (where this book lies) is sparsely populated, if not in principle then certainly on specific issues. James Franklin hews determinedly to logic and evidence in seeking to clarify what science can know and the degree of probability that scientific knowledge can attain. His discussion is unfailingly clear-headed and thought-provoking, and the range of material he draws on is impressive.